Vertical Deformation of Manikin Asphalt Concrete Core Dam Using Mohr-Coulomb and Hardening Soil Material Models with Plaxis 2D Software - Arya Bakti Gewangga; Kresno Wikan Sadono (TEKNIK, 2025)
The Manikin Dam, located in Taebenu District, Kupang Regency, East Nusa Tenggara Province, is currently under construction. The dam is designed with an asphalt concrete core. The initial foundation elevation of the Manikin Dam was set at 103 meters above sea level due to fluctuating NSPT values. Consequently, the Dam Safety Commission recommended lowering the foundation elevation to 98 meters above sea level. This study aims to analyze the relationship between vertical deformation and stability in the Manikin Dam design at different foundation elevations. The modeling was conducted using Plaxis 2D V22, simulating asphalt concrete with two material models: Mohr-coulomb and hardening soil.The analysis results indicate that as the embankment height increases at different foundation elevations, the safety factor decreases while vertical deformation increases. At the final stage of embankment construction, the vertical deformation of the Manikin Dam at a foundation elevation of 103 meters for the mohr-coulomb core material model is 35.12 cm with a safety factor of 1.723, whereas, for The hardening soil core material model, it is 35.74 cm with a safety factor of 1.720. At a foundation elevation of 98 meters, the vertical deformation is 35.81 cm for the mohr-coulomb core material model with a safety factor of 1.715 and 36.69 cm for The hardening soil core material model with a safety factor 1.724. The safety factor and vertical deformation values for the dam core using both the mohr-coulomb and hardening soil material models remain within permissible limits.